Pengaruh Media E Flash Card Terhadap Keterampilan Membaca Permulaan Siswa Kelas II SD Negeri Lonrong Kecamatan Bajeng Kabupaten Gowa - Andi Paida; Sri Rahayu, Multasyam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
II Students of Lonrong Elementary School, Bajeng District, Gowa Regency. Thesis. Elementary School Teacher Education Department, Teacher Training and Education Faculty, Muhammadiyah University of Makassar. Supervisor I Andi Paida. and Supervisor II Sri Rahayu. This study aims to determine the Effect of E FLASH CARD Media on Beginning Reading Skills of Grade II Students of Lonrong Elementary School, Bajeng District, Gowa Regency in the 2024/2025 academic year. This study uses an experimental method, a one group pretest posttest design type of research design, namely an experiment that in its implementation only involves one class as an experimental class. The experimental unit in this study was 40 grade II students. The results of inferential statistical analysis using the t-test formula, it is known that the t-count value obtained is 9.533 with a frequency of db = 40- 1 = 39, at a significant level = 0.05 obtained tTable = 2.019 so, tCount> tTable or the Null Hypothesis (H0) is rejected and the Alternative Hypothesis (H1) is accepted. This proves that the use of E Flash Card